Efficient Microstrip Bandpass Filter Design by a Surrogate-Model-Assisted Improved Decomposition-Based Multi-Objective Differential Evolution Algorithm - Wang, Zeyu; Zhang, Lu; Li, Kun-Lai; Zhang, Yongliang (International Conference on Numerical Electromagnetic Modeling and Optimization for RF, Microwave, and Terahertz Applications (Online), 2025)
A one-dimensional convolutional autoencoder (1D-CAE) assisted improved decomposition-based multiobjective differential evolution (IMODEA/D) algorithm is proposed for electromagnetic (EM) optimization in microstrip bandpass filter design. The 1D-CAE is employed as a surrogate model to accelerate the design process. In addition, the convergence of the MOEA/D algorithm is improved by adding extreme value optimization and modifying the individual selection, mutation probability, boundary optimization strategy and replacing the crossover operation in the differential evolution (DE) algorithm with the simulated binary crossover (SBX). The efficiency of the proposed method is verified by a planar microstrip bandpass filter.